Numb chin syndrome associated with residual ridge resorption in edentulous mandible: Report of a case - AKKİTAP, MELDA PELİN; GÜMRÜ TARÇIN, BİRSAY (My University, 2022)
Residual ridge resorption (RRR), which follows a chronic, progressive, and irreversible course, is due to alveolar remodeling under the influence of cumulative effect of many local and systemic factors after tooth extraction. Decreased height of the mandible leads to change in the location of the mental foramina at the crest of the residual ridge and also subjective pain and paresthesia under mandibular dentures due to the pressure caused by the denture, a phenomenon known as “numb chin syndrome”. In this article, a case with excessive mandibular RRR is presented along with clinical and radiological findings. Clinical and radiological examinations of a 61-year-old female patient who admitted to our clinic with tenderness and soreness complaints in the right mandibular edentulous alveolar ridge were performed. Intraoral examination revealed severe resorption of the edentulous mandibular alveolar ridge. The right mental foramen was observed to be close to the alveolar crest in panoramic radiograph. Cone beam computed tomography scan confirmed the severe mandibular atrophy and mental foramen exposure at the top of the alveolar crest, clearly revealing the cause of the patient’s tenderness and soreness complaints. In the edentulous mandible, RRR predisposes the mental nerve to injury because of the proximity of the mental foramina to the alveolar crest. Chronic pressure on the mental nerve may cause pain in the mental nerve distribution region and numbness in the lower lip. Radiographic examinations should definitely be considered as an indispensable component of diagnosis and prosthetic treatment planning, especially in edentulous patients with RRR

Kronik, progresif ve irreversibl bir seyir izleyen rezidüel kret rezorpsiyonu (RKR), diş kaybı sonrası birçok lokal ve sistemik faktörün kümülatif etkisi altındaki alveolar remodelinge bağlıdır. Mandibula yüksekliğinin azalması; mental foramenin rezidüel kretteki lokalizasyonunun değişmesine ve “uyuşuk çene sendromu” olarak bilinen mandibular protezlerin baskısı nedeniyle subjektif ağrı ve parestezi ortaya çıkmasına yol açar. Bu olgu sunumunda; mandibulada şiddetli RKR mevcut olan ve subjektif ağrı ve parestezi şikayeti ile başvuran hastanın klinik ve radyolojik bulguları sunulmaktadır. Sağ mandibular dişsiz alveoler krette hassasiyet ve ağrı şikayeti ile kliniğimize başvuran 61 yaşındaki kadın hastanın klinik ve radyolojik muayenesi gerçekleştirilmiştir. İntraoral muayenede, dişsiz mandibular alveol kretinde şiddetli rezorpsiyon saptanmıştır. Panoramik radyografide, sağ mental foramenin alveol kret tepesine çok yakın lokalize olduğu izlenmiştir. Konik ışınlı bilgisayarlı tomografi görüntülemesi mandibuladaki şiddetli atrofiyi ve her iki taraftaki mental foramenin kret tepesinde konumlandığını doğrulayarak hastanın hassasiyet ve ağrı şikayetinin nedeni açıkça ortaya koymuştur. Dişsiz mandibulada RKR, mental foramenin alveolar kret tepesine yakın konumlanmasından dolayı mental sinirin zarar görmesine yol açabilir. Mental sinirin kronik baskıya maruz kalması, mental sinirin dağılım bölgesinde ağrı ve alt dudakta uyuşukluk şikayetine neden olabilir. Özellikle RKR mevcut olan dişsiz ağızlarda, detaylı radyolojik inceleme kesinlikle tanı ve protetik tedavi planlamasının önemli bir bileşeni olarak düşünülmelidir
Dişsiz mandibulada rezidüel kret rezorpsiyonu ile ilişkili uyuşuk çene sendromu: Bir olgu sunumu
Keywords: Rezidüel kret rezorpsiyonu; mental foramen; dişsiz mandibula; uyuşuk çene sendromu; konik ışınlı bilgisayarlı tomografi; Residual ridge resorption; edentulous mandible; numb chin syndrome; cone beam computed tomography